Effects of 1, 25(OH)2D3 and 25(OH)D3 on C2C12 Myoblast Proliferation, Differentiation, and Myotube Hypertrophy. Issue 11 (14th April 2016) - van der Meijden, K.; Bravenboer, N.; Dirks, N.F.; Heijboer, A.C.; den Heijer, M.; de Wit, G.M.J.; Offringa, C.; Lips, P.; Jaspers, R.T.
Abstract : An adequate vitamin D status is essential to optimize muscle strength. However, whether vitamin D directly reduces muscle fiber atrophy or stimulates muscle fiber hypertrophy remains subject of debate. A mechanism that may affect the role of vitamin D in the regulation of muscle fiber size is the local conversion of 25(OH)D to 1, 25(OH)2 D by 1α‐hydroxylase. Therefore, we investigated in a murine C2C12 myoblast culture whether both 1, 25(OH)2 D3 and 25(OH)D3 affect myoblast proliferation, differentiation, and myotube size and whether these cells are able to metabolize 25(OH)D3 and 1, 25(OH)2 D3 . We show that myoblasts not only responded to 1, 25(OH)2 D3, but also to the precursor 25(OH)D3 by increasing their VDR mRNA expression and reducing their proliferation. In differentiating myoblasts and myotubes 1, 25(OH)2 D3 as well as 25(OH)D3 stimulated VDR mRNA expression and in myotubes 1, 25(OH)2 D3 also stimulated MHC mRNA expression. However, this occurred without notable effects on myotube size. Moreover, no effects on the Akt/mTOR signaling pathway as well as MyoD and myogenin mRNA levels were observed. Interestingly, both myoblasts and myotubes expressed CYP27B1 and CYP24 mRNA which are required for vitamin D3 metabolism. Although 1α‐hydroxylase activity could not be shown in myotubes, after treatment with 1, 25(OH)2 D3 or 25(OH)D3 myotubes showed strongly elevated CYP24 mRNA levels compared to untreated cells. Moreover, myotubes were able to convert 25(OH)D3 to 24R, 25(OH)2 D3 which may play a role in myoblast proliferation and differentiation. These data suggest that skeletal muscle is not only a direct target for vitamin D3 metabolites, but is also able to metabolize 25(OH)D3 and 1, 25(OH)2 D3 . J. Cell. Physiol. 231: 2517–2528, 2016. © 2016 The Authors. Journal of Cellular Physiology Published by Wiley Periodicals, Inc. Abstract : In differentiating C2C12 myoblasts and myotubes, 1, 25(OH)2D3 as well as 25(OH)D3 stimulate VDR mRNA expression and in myotubes 1, 25(OH)2D3 also stimulates MHC mRNA expression, however, this occurs without notable effects on expression of myogenic regulatory factors, the Akt/mTOR signaling pathway and myotube size. Interestingly, both differentiating myoblasts and myotubes express CYP27B1 and CYP24 mRNA and myotubes are able to synthesize 24R, 25(OH)2D3 from 25(OH)D3. These data suggest that skeletal muscle is not only a direct target for vitamin D3 metabolites, but is also able to metabolize 25(OH)D3 and 1, 25(OH)2D3.